Severe Acute Respiratory Syndrome Coronavirus 2 Seroprevalence Survey Among 17 971 Healthcare and Administrative Personnel at Hospitals, Prehospital Services, and Specialist Practitioners in the Central Denmark Region. (3rd October 2020) - Jespersen, Sanne; Mikkelsen, Susan; Greve, Thomas; Kaspersen, Kathrine Agergård; Tolstrup, Martin; Boldsen, Jens Kjærgaard; Redder, Jacob Dvinge; Nielsen, Kent; Abildgaard, Anders Mønsted; Kolstad, Henrik Albert; Østergaard, Lars; Thomsen, Marianne Kragh; et al.
Abstract: Background: The objective of this study was to perform a seroprevalence survey on severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) among Danish healthcare workers to identify high-risk groups. Methods: All healthcare workers and administrative personnel at the 7 hospitals, prehospital services, and specialist practitioner clinics in the Central Denmark Region were invited to be tested by a commercial SARS-CoV-2 total antibody enzyme-linked immunosorbent assay (Wantai Biological Pharmacy Enterprise Co, Ltd, Beijing, China). Results: A total of 25 950 participants were invited. Of these, 17 971 had samples available for SARS-CoV-2 antibody testing. After adjustment for assay sensitivity and specificity, the overall seroprevalence was 3.4% (95% confidence interval [CI], 2.5%–3.8%). The seroprevalence was higher in the western part of the region than in the eastern part (11.9% vs 1.2%; difference: 10.7 percentage points [95% CI, 9.5–12.2]). In the high-prevalence area, the emergency departments had the highest seroprevalence (29.7%), whereas departments without patients or with limited patient contact had the lowest seroprevalence (2.2%). Among the total 668 seropositive participants, 433 (64.8%) had previously been tested for SARS-CoV-2 RNA, and 50.0% had a positive reverse-transcription polymerase chain reaction (PCR) result. Conclusions: We found large differences in the prevalence of SARS-CoV-2 antibodies in staff working in the healthcare sector within a small geographical area of Denmark. Half of all seropositive staff had been tested positive by PCR prior to this survey. This study raises awareness of precautions that should be taken to avoid in-hospital transmission. Regular testing of healthcare workers for SARS-CoV-2 should be considered to identify areas with increased transmission. Abstract : Severe acute respiratory syndrome coronavirus 2 seroprevalence among healthcare workers in the Central Denmark Region showed large geographical differences (1%–12%). The risk of infection was associated with workplace, rather than location of residence.